1997
DOI: 10.1142/s0217984997000931
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Hardness and Adhesion of Diamond-Like Carbon Films

Abstract: Diamond-like carbon films have been synthesized by the pulsed laser deposition under a magnetic field. The hardness of the films was increased considerably. However, due to the large compressive stress in the films, adhesion of the films became a serious problem. Two methods, i.e. laser irradiation of the silicon substrate surface and growing a composition-graded intermediate layer, were used to increase the adhesion. With the variations of the interface conditions, the change of the stress type from compressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…For the evaluation the adhesion properties of thin coatings, Chen-Gao (C-G) method was chosen. [12][13][14][15] This method introduces the composite hardness as a function of the critical reduced depth, b, beyond which the material will have no effect on the measured hardness. The critical reduced depth b represents the ratio between the radius of the plastic zone beneath the indentation and the indentation depth.…”
Section: Theory Of Composite Hardness and Adhesion Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the evaluation the adhesion properties of thin coatings, Chen-Gao (C-G) method was chosen. [12][13][14][15] This method introduces the composite hardness as a function of the critical reduced depth, b, beyond which the material will have no effect on the measured hardness. The critical reduced depth b represents the ratio between the radius of the plastic zone beneath the indentation and the indentation depth.…”
Section: Theory Of Composite Hardness and Adhesion Modelsmentioning
confidence: 99%
“…It has been shown that the micro-MECHANICAL CHARACTERIZATION OF ELECTRODEPOSITED COPPER COATINGS 731 hardness testing can be a useful technique in assessing the adhesion of thin films to the substrate. [11][12][13][14][15] The aim of the study was to analyze the hardness response of the selected composite systems and analyze the results of the quantitative assessment of coating adhesion based on the measured composite hardness.…”
Section: Introductionmentioning
confidence: 99%